ANALISIS KINERJA JARINGAN INTERNET KAMPUS MENGGUNAKAN METODE QOS (QUALITY OF SERVICE) - Syukriadi Syukriadi (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Campus internet is an essential infrastructure to support academic, research, and administrative activities. However, network performance often faces challenges such as slow access, unstable connections, and limited bandwidth capacity. This study aims to analyze the performance of the campus internet network using the Quality of Service (QoS) method based on the TIPHON standard, with a case study at Politeknik Pertanian Negeri Payakumbuh (PPNP). The analyzed parameters include delay, jitter, packet loss, and throughput. Measurements were carried out during peak hours and normal hours using Wireshark and bandwidth testing on Mikrotik devices. The results show that the average delay is 250 ms (medium category), jitter 35 ms (poor category), packet loss 1.5% (good category), and throughput 2.1 Mbps from 10 Mbps (poor category). Thus, the overall performance of the campus internet network falls into the medium to poor category. The main factors affecting performance are the high number of users, limited bandwidth capacity, and suboptimal network configuration. Recommended improvements include increasing bandwidth capacity, implementing traffic management with QoS policies on routers, and separating academic and administrative networks to enhance stability. Keywords: Campus Internet Network, Quality of Service, QoS, TIPHON, Politeknik Pertanian Negeri Payakumbuh.  Abstrak: Internet kampus merupakan infrastruktur penting dalam mendukung kegiatan akademik, penelitian, dan administrasi. Namun, kinerja jaringan sering kali mengalami kendala seperti akses lambat, koneksi tidak stabil, dan keterbatasan bandwidth. Penelitian ini bertujuan untuk menganalisis kinerja jaringan internet kampus menggunakan metode Quality of Service (QoS) berdasarkan standar TIPHON dengan studi kasus di Politeknik Pertanian Negeri Payakumbuh (PPNP). Parameter yang dianalisis meliputi delay, jitter, packet loss, dan throughput. Pengukuran dilakukan pada jam sibuk (peak hours) dan jam normal menggunakan aplikasi Wireshark dan pengujian bandwidth pada perangkat Mikrotik. Hasil penelitian menunjukkan bahwa rata-rata delay adalah 250 ms (kategori medium), jitter 35 ms (kategori poor), packet loss 1,5% (kategori good), dan throughput 2,1 Mbps dari 10 Mbps (kategori poor). Dengan demikian, kinerja jaringan internet kampus secara umum berada pada kategori medium to poor. Faktor utama yang memengaruhi adalah tingginya jumlah pengguna, keterbatasan kapasitas bandwidth, serta konfigurasi jaringan yang kurang optimal. Rekomendasi perbaikan adalah penambahan bandwidth, manajemen trafik dengan QoS policy di router, serta pemisahan jaringan akademik dan administratif untuk meningkatkan stabilitas. Kata kunci: Jaringan Internet Kampus, Quality of Service, QoS, TIPHON, Politeknik Pertanian Negeri Payakumbuh.